Representasi Gender Dalam Cerpen Sampan Zulaiha - Liza Handayani Batu Bara; Budiman Budiman (Pusat Riset dan Inovasi Nasional, 2024)
Gender representation is not only important in understanding characterization and dynamics of stories, but also in identifying narratives that govern and influence public perceptions of gender roles. The study aims to analyze gender representation in